Gender dysphoria in adolescence. (2nd January 2016) - Leibowitz, Scott; de Vries, Annelou L.C.
Abstract: Adolescents presenting with gender-related concerns are increasingly seeking support from providers from a variety of disciplines within health care settings across the world. For those treating young people who meet the criteria for the DSM 5 diagnosis of gender dysphoria (GD), complex decisions in clinical care are common. Defining best practice with this population with respect to interventions that span mental health, physical, and surgical domains can be challenging, given a relative dearth of empirical data available; yet practice guidelines have emerged from different professional organizations which can aid with this. For this review paper, a broad literature search was performed to identify relevant studies pertaining to the care of adolescents with GD. In addition, an overview of trends in clinical practice, including shifts in conceptualization of how clinicians and patients define care that is considered affirming when working with this population, is described. This paper explores the characteristics of referral patterns to specialized clinics, provides a brief overview of gender identity development in adolescence, and then describes the phenomenology of known aetiological factors and co-occurring psychiatric issues in adolescents with GD. Additionally, clinical management considerations that detail assessment aims and common treatment interventions across disciplines will be explored.